A Study of CO2 Absorption Using Jet Bubble Column - Setiadi, Setiadi; Hadiyani, Nita Tania; Hantizen, Hantizen; Supramono, Dijan (Makara Journal of Technology, 2008)
A Study of CO2 Absorption Using Jet Bubble Column. The phenomenon of plunging jet gas-liquid contact occurs quite often in nature, it's momentum carries small air bubbles with it into the reactor medium. The momentum of the liquid stream can be sufficient to carry small bubbles completely to the bottom of the vessel. A stream of liquid falling toward a level surface of that liquid will pull the surrounding air along with it. It will indent the surface of the liquid to form a trumpet-like shape. If the velocity of the stream is high enough, air bubbles will be pulled down, i.e. entrained into the liquid. This happens for two main reasons: air that is trapped between the edge of the falling stream and the trumpet-shaped surface profile and is carried below the surface. This study investigates the potential of a vertical liquid plunging jet for a pollutant contained gas absorption technique. The absorber consists of liquid jet and gas bubble dispersed phase. The effects of operating variables such as liquid flowrate, nozzle diameter, separator pressure, etc. on gas entrainment and holdup were investigated. The mass transfer of the system is governed by the hydrodynamics of the system. Therefore a clear and precise understanding of the above is necessary : to characterize liquid and gas flow within the system, 2. Variation in velocity of the jet with the use of different nozzle diameters and flow rates, 3. Relationship between the liquid and entrained airflow rate, 4. Gas entrainment rate and gas void fraction.